A Costly Loss of Heart: The Scholastic Notion of Voluntas Ut Natura - Downey, Michael (Philosophy & theology, 1987)
In using the term “heart” to describe that which is constitutive of human personhood, Jean Vanier gives evidence that he views the person largely as affective, open to attraction, to be acted upon by another and drawn to communion. This is not to suggest that the heart is irrational or anti-intellectual, or to suggest that Vanier’s vision of the human person is so. Rather it is to suggest that, for Vanier, all that is known and decided is to be shaped by the affective basis within the human person which needs to be touched by the Spirit. Maintaining the importance of intellect and reason, especially as these bear upon the social order, Vanier’s concern is with the core or ground of the human person which is antecedent to intellectual activity or rational discourse, and which, when touched by the presence of the Spirit, motivates one to the activity of the beatitudes. Those who respond to this action of the Spirit, and act from the heart when moved by God to compassion, become signs of God’s love, healing, tenderness and compassion.